Local and regional sources of urban ambient PM2.5 exposures in Calgary, Canada. (1st December 2022) - Anastasopolos, Angelos T.; Hopke, Philip K.; Sofowote, Uwayemi M.; Zhang, Joyce J.Y.; Johnson, Markey
Abstract: Ambient fine size fraction particulate matter (PM2.5 ) sources in the western Canada city of Calgary, Alberta were identified and their contributions quantified for 2015–2019 based on elemental and ion composition data from sampling at a central monitoring site and the US Environmental Protection Agency Positive Matrix Factorization (v5.0) receptor model. Meaningful source apportionment results were obtained by using reconstructed PM2.5 mass and an estimated unmeasured mass in absence of carbonaceous component measurements. Auxiliary analyses identified source regions. Identified source types and average contribution to PM2.5 were secondary organic aerosol (24%), wood smoke (16%), soil/crustal matter (15%), traffic/rail (14%), particulate sulfate (13%), particulate nitrate (10%), and road salt/aged road salt (9% combined). Calgary PM2.5 contributions of secondary organic aerosol, particulate sulfate, and traffic/rail sources were similar to the next-nearest western city of Edmonton while particulate nitrate contributions were lower, wood smoke impacts greater and other factors showed greater inter-city differences. Secondary PM2.5 contributions in Calgary were consistent with estimates for medium and large cities in central Canada for SOA and particulate nitrate but lower for particulate sulfate. Primary wood smoke PM2.5 contributions were consistent with other Canadian cities and confirmed strong influence of winter season biomass burning. Combined on-road vehicle and rail transportation activity were found to contribute comparably more to ambient PM2.5 in Calgary than in central Canadian cities. Soil/crustal re-suspension/transport and intensive winter-time use of road salts were also important local PM2.5 sources. Several factors were characterized by local sources (traffic/rail, soil/crustal matter, road salt, aged road salt, wood smoke) with episodic regional source contributions (wood smoke, soil/crustal matter) and secondary aerosol factors (SOA, particulate sulfate, particulate nitrate) also demonstrated influence from local sources alongside regional source contributions, indicating that Calgary ambient PM2.5 concentrations are likely strongly influenced by local source emissions. These findings present positive opportunities for multiple air quality management and source mitigation strategies, including at the local/municipal level. Graphical abstract: Image 1 Highlights: Receptor modelling identified PM2.5 sources and contributions for Calgary, Canada. Use of unmeasured mass variable augmented partial compositional data. Primary and secondary aerosol sources were apportioned. Traffic/rail, soil/crustal, and winter road salt source contributions were high. Local source emissions likely strongly influence Calgary ambient PM2.5 .